2006
DOI: 10.1016/j.pbi.2006.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting scents of distress: the prospect of manipulating herbivore-induced plant odours to enhance the control of agricultural pests

Abstract: In response to feeding by arthropods, plants actively and systemically emit various volatile substances. It has been proposed that these herbivore-induced volatiles (HIPVs) can be exploited in agricultural pest control because they might repel herbivores and because they serve as attractants for the enemies of the herbivores. Indeed, recent studies with transgenic plants confirm that odour emissions can be manipulated in order to enhance the plants' attractiveness to beneficial arthropods. An additional advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
176
0
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(192 citation statements)
references
References 52 publications
(75 reference statements)
0
176
0
9
Order By: Relevance
“…It is well known that manipulation of volatile emission in plants has enormous potential in relationship to pest management in agricultural contexts [43]. Manipulating these signals may help increase the effectiveness of attracting parasitoid and predatory natural enemies with induced VOCs to more effectively serve as biological control agents in agroecosystems.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…It is well known that manipulation of volatile emission in plants has enormous potential in relationship to pest management in agricultural contexts [43]. Manipulating these signals may help increase the effectiveness of attracting parasitoid and predatory natural enemies with induced VOCs to more effectively serve as biological control agents in agroecosystems.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Hence, this study suggests that parasitoids do not use all herbivore-induced VOCs for habitat and host location to a similar degree, but rather pay selective attention to a few compounds. Identifying these key compounds seems crucial for a good understanding of the host searching process in parasitoids and for the development of strategies to increase the efficiency of natural enemies for the control of pest insects (Turlings and Ton, 2006).…”
Section: Attractiveness Of Shikimic Acid Derived Vocsmentioning
confidence: 99%
“…Typically, insect attack leads to an increase in emission of plant volatile compounds that appear to function as a 'cry for help' to attract natural enemies in tritrophic interactions (Takabayashi & Dicke 1996;de Moraes et al 1998;Du et al 1998;Turlings & Ton 2006;Heil 2008) and repel further colonization by the herbivore itself (de Moraes et al 2001;Kessler & Baldwin 2001). Recently, it has been observed that plants increase volatile emission even at the earliest stage of herbivore attack, namely oviposition (Colazza et al 2004;Hilker & Meiners 2006).…”
Section: Introductionmentioning
confidence: 99%